Pre-operative antibiotics in patients with acute mild cholecystitis undergoing laparoscopic cholecystectomy: is it really useful? A systematic review - Camilo Ramírez-Giraldo; Isabella Van-Londoño; Antonio Pesce (World Journal of Emergency Surgery)
Abstract Background Empirical antibiotic therapy is often initiated during the hospital stay while awaiting laparoscopic cholecystectomy. This approach is generally justified in patients with moderate (Tokyo II) and severe (Tokyo III) acute cholecystitis, where organ dysfunction occurs as a result of the inflammatory or infectious process. However, there is no clear consensus regarding the use of antibiotics in patients with mild (Tokyo I) cholecystitis. This study aimed to evaluate the impact of preoperative antibiotic use on outcomes in patients with acute cholecystitis. Methods A systematic review of PubMed, Embase and Cochrane was conducted following the PRISMA methodology. Studies were eligible for inclusion if they were randomized controlled trials or non-randomized comparative studies evaluating the use or non-use of preoperative antibiotics in patients with acute cholecystitis. Eligible studies were required to provide at least one of the following datasets: postoperative complication rate, postoperative infectious complication rate, or positive culture rate. The synthesis reports were prepared using the Synthesis Without Meta-analysis (SWiM) framework. Results A total of 622 articles were initially identified, of which 2 met the inclusion criteria. These two articles included 331 patients. They reported higher rates of postoperative complications and bacterobilia in the group that received preoperative antibiotics; however, the differences were not statistically significant (p > 0.05). Conclusion Based on current evidence, no recommendation can be made regarding the therapeutic use of antibiotics in mild acute cholecystitis while awaiting laparoscopic cholecystectomy.